UPAYA PENANGGULANGAN NARKOBA DI KALANGAN MILENIAL MENUJU GENERASI EMAS YANG UNGGUL - Sania Dinda Awalia; Neili Winda Saharani; Amalia Nur Chasanah; Tri Esti Rahayuningtyas; Widyatmoko Widyatmoko (BADAN PENERBIT STIEPARI PRESS, 2021)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semi-synthetic, which can cause a decrease or change in consciousness, loss of taste, reduce to eliminate pain, and can cause dependence, which are divided into groups as attached in the Law. This (according to Article 1 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics). The purpose of this research is to examine what makes millennials abuse drugs and find solutions to dealing with drugs for the sake of the golden generation. For the research method used is data reduction and data presentation. The results of this study indicate that there are many factors that influence the millennial generation to abuse drugs, including personality, family, environment, education, society and social community factors.